Do admit! : the Mitford sisters and me - Pond, Mimi (Drawn & Quarterly, 2025)
Born with pedigrees but without the pocketbooks to match, The Mitfords were certainly no strangers to lies, intrigue, or scandal. Nancy, Pamela, Diana, Unity, Jessica, and Deborah. All six sisters were weaned on their family's well-documented upper class eccentricities: a ne'er do well would-be entrepreneur father; a stern, stiff-upper-lipped mother; a revolving door of governesses of varying propriety, all against the backdrop of a crumbling estate falling into disrepair. The sisters grew from cloistered turn-of-the-century country girls into debutantes who would marry into political influence -- for better or worse. Is it any wonder that a young, working class Mimi in Southern California becomes enamored with The Mitfords' downright fanciful rich-and-famous lifestyle? This charming, inventively cartooned, and lovingly researched biography captures the dramatic, over-the-top antics of high society's strongest personalities as they rubbed elbows with some of history's most infamous fascists and communists. Pond's genius for classic cartooning in the vein of the Vanity Fair caricature and the satirical illustrations of Charles Addams brings the aesthetic decadence of the 1920s and '30s to life with effortless aplomb, warts and all.